Reassessing the Confluence Model of Men's Risk for Sexual Aggression. Issue 7 (April 2023) - Yucel, Ebru; Angelone, D. J.; Jones, Meredith C.
Reassessing the confluence model of men's risk for sexual aggression—the confluence model of sexual aggression has been widely used to study men's risk for perpetrating sexual violence. Over time, researchers have attempted to expand this model to improve its predictive utility. Unfortunately, this work has continued to produce similar results with only slight improvements in prediction at best. One explanation for the inability to enhance the model could be due to changes in the dating landscape and shifts in beliefs about gender roles. Therefore, the current study aims to reassess the confluence model using a more contemporary construct, hostile sexism, in an effort to improve the predictive utility of the confluence model of sexual aggression. Participants were 258 college men recruited from a medium-sized public university in the northeastern United States, using an online participant pool of students who volunteered to participate as part of a requirement for a psychology course. Structural equation modeling using mean- and variance-adjusted weighted least squares estimation indicated that the confluence of hostile sexism and impersonal sex appears to be a better predictor of sexual aggression in comparison to the confluence of hostile masculinity and impersonal sex. The results suggest that replacing hostile masculinity with hostile sexism may produce a model that is better able to predict men's risk for perpetrating sexual aggression. These results can provide insight for future iterations of the confluence model, which may include hostile sexism as a core construct. Attitudes that stem from hostile sexism may be a beneficial target for future interventions designed to decrease the frequency of perpetration.